Manajemen Mutu Terpadu ( Total Quality Management / TQM ) - Mohammad Juhri; Zainab Nurlaili; Ali Nurhadi (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
The current quality concern is one that affects an organization's ability to survive. Quality must be prioritized in all areas of the organization, including education, if it is to remain sustainable. As a result, quality assurance is very important and must be implemented in businesses using the Total Quality Management (IQM) framework. qualitative The essence of Integrated Quality Management (MMT) is a method for continuously improving services or goods to achieve customer satisfaction. MMT strategy, making it comprehensive. Technical considerations are only one aspect of quality, the extent to which customer requirements are met is another. MMT also pays attention to non-physical aspects such as corporate culture, leadership style, and followers. Service quality will be improved and given a deeper meaning by the integration of these aspects.